Complications of Cataract Surgery Following Phacoemulsification and Foldable Intraocular Lens Implantation in Dogs - Chauhan, Darshan J; Talekar, Shivaji H; Patel, Krina D; Rokad, Hardik A; Bhatt, Raghuvir H; Vadalia, Jignesh V; Kumar, Vishnudeo (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Cataracts are the most common treatable cause of visual impairment and blindness in dogs. Despite tremendous improvements in canine cataract surgery over the years, numerous intra- and post-operative complications persist and decrease the success rate of cataract surgery. The present study was conducted on 12 eyes of 12 distinct dogs presented to Department of Veterinary Surgery and Radiology of the College in Junagadh (Gujarat) to evaluate intra- and post-operative complications after phacoemulsification and intra-ocular lens implantation. Prior to surgery, all dogs were subjected to a detailed ophthalmic examination along with routine clinical, haematological and serum biochemical analysis. In all twelve dogs, phacoemulsification technique was utilised for the surgical removal of the cataractous lens and implantation of intra-ocular lens under premedication with Atropine sulphate, induction with combination of Ketamine-Diazepam and maintenance with Isoflurane. Intra-operative complications recorded were radial tear during continuous curvilinear capsulotomy, miosis, chemosis, hyphema and post-operative complications recorded were corneal opacity, corneal edema, uveitis, ocular hypertension and bullous keratopathy.
Keywords: Cataract; Complications; Dogs; Intraocular lens; Phacoemulsification